Competency and Training Management Toward Civil Servant Performance via Retention Mediation - Irwan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Improving the quality of human resources in the public sector is essential to ensure effective and efficient government services, particularly at the sub-district level, which serves as the frontline in public administration. Civil Servants (PNS) are required to demonstrate optimal performance to meet these demands. One strategic approach involves strengthening talent management, developing competencies, and providing targeted job training. This study aims to analyze the influence of talent management, competencies, and job training on civil servant performance at the sub-district level in Makassar City, with employee retention as a mediating variable. A quantitative method with a survey approach was used, involving 385 civil servants selected through random sampling. Data collection was conducted using a structured questionnaire, and analysis was carried out using Structural Equation Modeling (SEM) with AMOS software. The results show that talent management, competencies, and job training each have a positive and significant effect on both employee retention and performance. Additionally, employee retention significantly mediates the relationship between these factors and performance. These findings highlight the importance of integrated and continuous human resource management strategies to enhance public service performance through improved employee retention.